(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Watermelon, a popular fruit known for its refreshing taste and nutritional benefits, is widely consumed for its rich vitamin C content and high water percentage. Despite its popularity, there is limited research on the extent of knowledge among health science students regarding its detailed nutritional value and associated health benefits. This study aims to assess the level of nutritional knowledge and awareness of the health benefits of watermelon among students at the College of Health Sciences and Technology, Ofuoma Ughelli, Delta State. The specific objectives include evaluating students’ understanding of watermelon’s basic and specific nutritional components and identifying gaps in knowledge about its health benefits. A descriptive cross-sectional survey was conducted involving 190 students from the College of Health Sciences and Technology, Ofuoma Ughelli. Data were collected using structured questionnaires that covered demographic information, knowledge of watermelon’s nutritional content, and awareness of its health benefits. The collected data were analyzed using descriptive statistics, including frequency counts and percentages. The study revealed that a significant majority of students possess a good understanding of the basic nutritional components of watermelon. For instance, 90.0% of the respondents correctly identified that watermelon is rich in vitamin C, and 92.4% were aware of its high water content. However, knowledge about specific nutrients such as lycopene and citrulline was less comprehensive, with only 71.1% and 56.9% awareness respectively. Similarly, while most students (94.8%) acknowledged the hydration benefits of watermelon, fewer were aware of its cardiovascular (64.0%) and cancer-preventive (61.6%) properties. The findings indicate that while there is a strong foundational knowledge of watermelon’s basic nutritional benefits among students, there are significant gaps in understanding its more specific health benefits. This underscores the need for enhanced nutrition education, focusing on the detailed health benefits of fruits like watermelon. The study recommends integrating comprehensive nutrition modules into the curriculum, organizing workshops, and providing accessible educational materials to bridge these knowledge gaps.